A method to predict vortex shedding response based on Vickery and Basu model: A proposal for the new Brazilian Wind Code. (1st November 2019) - Grala, Pedro; Loredo-Souza, Acir Mércio; Rocha, Marcelo Maia
Highlights: It presents the development of a method to predict the vortex shedding response. This method works well for all ranges of the relation structural/aerodynamic damping. Method uses coefficients that vary with turbulence intensity and Reynolds number. Abstract: Structures like towers and industrial chimneys are quite vulnerable to the vortex shedding phenomenon, due to their slenderness and non-aerodynamic form. Furthermore, due to their low structural damping, these structures are also more likely to reach large displacement amplitudes, which is caused by the lock-in effect. Although these structures are considered simple from structural and aerodynamic viewpoints, the study of cross-wind vibrations in these structures is quite complicated, as involves the interaction of complex topics of fluid and structural mechanics, turning a reliable determination of the structural response into one of the most complicated problems in Wind Engineering. In the 1980s, Vickery and Basu proposed a model that is the base of many methods in codes and standards, but these methods do not consider all parameters that affect such phenomenon. This study aims to present a proposal for the new Brazilian Wind Code based on Vickery and Basu Model to predict the response of circular structures, considering both large and small amplitude and creating more accurate coefficients. First, Vickery and Basu equation is simplified, and new coefficients are created based on existing studies. Then, these coefficients are compared with those exposed in other wind codes and standards. This comparison shows that the proposed coefficients are calibrated, and also are applicable to situations that are ignored by other wind codes and standards. The main improvement of this method is the consideration of the variation of the correlation length with Reynolds number and turbulence intensity, which create more accurate and safe coefficients.